The Influence of Professional Competence on the Authentic Assessment Skills of Indonesian Language Teachers at MTS Pekanbaru City - Nur Raudhoturrahmah; Desi Sukenti (JPP (Jurnal Pendidikan dan Pembelajaran))
This research aims to examine the influence of professional competence on the authentic assessment skills of Indonesian language teachers at MTS Pekanbaru City. This type of research is quantitative with a correlation method. The population in this study were MTS Indonesian language teachers in Pekanbaru city. Samples were taken randomly with a total sample of 52 teachers. Data collection techniques are questionnaires, documentation and observation. The analysis used is validity, reliability and prerequisite tests. Hypothesis testing was carried out using a correlation test with the help of the SPSS version 25 program. The research results showed that professional competence had a positive and significant influence on authentic assessment skills with a correlation test result of R= 0.678. So it can be concluded that the professional competence possessed by Indonesian language teachers at MTS Pekanbaru city has an influence on authentic assessment skills, professionally competent teachers have the ability to assess and evaluate students, one of which is carrying out authentic assessment in Indonesian language subjects with the aim of measure students' abilities in various possible solutions to problems faced in real world situations or contexts that appear as the end result of a learning process.